EDUCATIONAL ACADEMIC SUPERVISION PRACTICE - Asri Yuni Vika Sari; Enung Nugraha, Agus Gunawan (Adisam Publisher, 2023)
An educational institution in improving the quality of education requires one of them is supervise, leaders in the educational environment play a role in the process of supervising and coaching the quality of teaching, learning and academic results of students. The purpose of writing this article is to explain the concept of academic supervision and the implementation of academic supervision which includes: planning, implementation and evaluation or follow-up. The method used in this article is qualitative, while the approach uses literature studies.where the author seeks information through articles in national journals with the keyword